2018
DOI: 10.1002/hep.30031
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Autoimmune Hepatitis and Its Treatment on Health Utility

Abstract: Our data show evidence of HRQOL impairment in a large cohort of AIH patients compared with the general population. Furthermore, corticosteroid use is strongly associated with decreased HRQOL, independent of remission status. This highlights the need for better corticosteroid-free therapy approaches and it emphasizes the need for future novel therapeutic trials in AIH. (Hepatology 2018; 00:000-000).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 47 publications
4
65
2
3
Order By: Relevance
“…Therefore, similar to patients with PBC, overtreatment with steroids deserves our attention in clinical practice. In general, health-related quality of life is impaired in patients with AIH, and steroid treatment has been found to be associated with an even further reduction of health-related quality of life and with a promotion of depressive symptoms [28,29]. Similar to PBC, the rate of patients with AIH adequately treated declined with increasing age (▶ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, similar to patients with PBC, overtreatment with steroids deserves our attention in clinical practice. In general, health-related quality of life is impaired in patients with AIH, and steroid treatment has been found to be associated with an even further reduction of health-related quality of life and with a promotion of depressive symptoms [28,29]. Similar to PBC, the rate of patients with AIH adequately treated declined with increasing age (▶ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic corticosteroid use in patients with autoimmune hepatitis is also strongly associated with detrimental effects on patients' quality of life, independent of remission status, notably as a cause of lower levels of utility, i.e. mobility and ability to perform usual activities (Wong et al, 2018). In another study, a high proportion of patients with autoimmune hepatitis reported significant impairment of mental health components of their quality of life, i.e.…”
Section: -4 Weeksmentioning
confidence: 97%
“…Currently, the approach of induction and maintenance of remission with corticosteroids and azathioprine with the aim of corticosteroid‐free remission on azathioprine monotherapy has a strong evidence base. Despite this, a significant proportion of patients do not achieve corticosteroid‐free remission, 12 experience a significant burden of side effects 13‐15 and have high rates of relapse both on treatment and following cessation of therapy 13,219 . In patients with preserved hepatic synthetic function and without evidence of advanced liver disease, it may be acceptable to conduct non‐inferiority studies comparing newer agents against corticosteroids for the induction of remission, especially once evidence of efficacy is observed in nonresponders, as delay in remission is unlikely to be associated with adverse outcomes.…”
Section: Experimental Approach In Aihmentioning
confidence: 99%
“…Despite a long established evidence base for first‐line therapy consisting of azathioprine and corticosteroids, and broadly agreed second‐line therapy with mycophenolate mofetil (Table 1), 15%‐20% of patients are intolerant of, nonresponsive to or have a contraindication to taking these therapies 12 . Both active disease and side effects from the currently available treatments are now recognised to have a significant negative impact on quality of life for patients, with corticosteroids being associated with the greatest reduction in health utility 13‐15 . There is active interest in developing novel therapies that may reduce disease activity, enhance immune tolerance and avoid the adverse consequences associated with corticosteroid use in AIH.…”
Section: Introductionmentioning
confidence: 99%